1999
DOI: 10.1104/pp.121.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Suberization-Associated Anionic Peroxidase of Potato

Abstract: The anionic peroxidase associated with the suberization response in potato (Solanum tuberosum L.) tubers during wound healing has been purified and partially characterized at the biochemical level. It is a 45-kD, class III (plant secretory) peroxidase that is localized to suberizing tissues and shows a preference for feruloyl (omethoxyphenol)-substituted substrates (order of substrate preference: feruloyl > caffeoyl > p-coumaryl Ϸ syringyl) such as those that accumulate in tubers during wound healing. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(103 citation statements)
references
References 49 publications
2
100
0
1
Order By: Relevance
“…The higher PPO activity might be associated with better rooting ability in treated cuttings, which was also consistent with data reported by Rout [32,52]. POD are known to be involved in auxin metabolism as well as lignification processes in the cell wall in the presence of phenol [53,54], and our data showed that the decrease of POD activity in NAA-treated tissues ( Figure 3B of adventitious roots in NAA-treated hypocotyls [44]. Moncousin et al [55] reported that low POD corresponded to high IAA levels before the visible appearance of roots.…”
Section: Discussionsupporting
confidence: 79%
“…The higher PPO activity might be associated with better rooting ability in treated cuttings, which was also consistent with data reported by Rout [32,52]. POD are known to be involved in auxin metabolism as well as lignification processes in the cell wall in the presence of phenol [53,54], and our data showed that the decrease of POD activity in NAA-treated tissues ( Figure 3B of adventitious roots in NAA-treated hypocotyls [44]. Moncousin et al [55] reported that low POD corresponded to high IAA levels before the visible appearance of roots.…”
Section: Discussionsupporting
confidence: 79%
“…Peroxidases are also involved in suberin formation through a similar process (Bernards et al 1999;Keren-Keiserman et al 2004). …”
Section: Lignification and Suberisationmentioning
confidence: 99%
“…Lignification near the site of injury is a defense response of plants after wounding (Toivonen and Brummell, 2008;Vance et al, 1980). Strengthening of the plant cell wall induced by POD was reported in potatoes (Bernards and Razem, 2001;Bernards et al, 1999), beet root and sugar beet (Waldron et al, 1997), and Chinese water chestnut (Parr et al, 1996). In addition, no meristematic tissue or periderm layers were found in young, peeled galangal rhizomes after 72 h. As a result, POD may be involved in lignin synthesis via strengthening the cell walls of parenchyma cells in the exterior tissue of the galangal rhizome (Fig.…”
Section: Browning Of Fresh-cut Galangalmentioning
confidence: 99%